Doppler ultrasound of umbilical artery in prediction of fetal outcome in pregnancy induced hypertension Sudanese population - Yousif, Rihab A.; Suliman, Awadia G.; Aburaida, Raga A.; Daoud, Ibrahim M.; Mohammed, Naglaa E. (International Journal of Research in Medical Sciences, 2019)
The pregnancy induced hypertension increase the fetal mortality and morbidity and the using of Doppler umbilical artery indices decrease the fetal mortality and morbidity however, there is few complete data about the most frequently altered Doppler US parameters to predict fetal outcome in pregnancy induced hypertension . Methods This ia cohort prospective study done in two hundred and six women of second and third trimester presenting to antenatal clinic in Soba University Hospital at the department of Obstetrics & Gynecology, in the fetus unit and critical pregnancy in the period From June 2008 to April 2013 to assess the Doppler indices of umbilical artery in pregnancy induced hypertension for prediction of prenatal outcome; 105 pregnancy induced hypertension patients and 101 women with uneventful pregnancies as normal control group included in this study . Baseline investigations and color Doppler of umbilical artery were done. Statistical analysis of data were done using SPSS, Receiver Operating Characteristic (ROC) curve analysis was performed and the area under the curve (AUC) used to determine sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of umbilical artery Doppler indices to predict fetal outcome. Results The study determine that there was significant difference in Doppler indices in PIH and control group ( p<0.01, the mean indices of umbilical artery is higher in PIH group compared with normal pregnancy group , the mean different of S/D ratio was 0.40, mean difference of RI was 0.06 and the mean different of PI index was 0.16, high percentage of adverse fetal outcome had been reported in in Pregnancy Induced Hypertension group than in control , which was more in absent and reversed flow velocity in umbilical artery in Pregnancy Induced Hypertension compared with group of Pregnancy Induced Hypertension with present end diastolic flow velocity. Systolic/Diastolic ratio was most accurate in predicting adverse outcome in pregnancy induced hypertension patients, followed by the Pulastility index then the Resistance index (75%, 66% and 57% respectively). Conclusion This study concluded that pregnancy induced hypertension leads to worsen placental insufficiently, which appears on the higher Doppler indices of umbilical artery to PIH patients when compared with normal pregnancy. A low diastolic flow and higher indices characterized the pregnancies with abnormal outcomes. Doppler of the umbilical artery was useful to predict fetal well being in PIH patients, high percentage of adverse fetal outcome had been reported in absent and reversed end diastolic flow velocity in umbilical artery compared with group of present flow velocity.